Assessment of biosafety measures in clinical laboratories of Al-Madinah city, Saudi Arabia - Omar Falah Khabour; Khalil H. Al Ali; Jamal N. Aljuhani; Mousa A. Alrashedi; Fuaad H. Alharbe; Ahmed Sanyowr (Journal of Infection in Developing Countries)
Introduction: Workers in clinical laboratories are exposed to occupational hazards on a daily basis and their health and safety may be threatened if appropriate protective standards are not implemented. The aim of this study was to assess the knowledge and practices of clinical laboratory workers towards biosafety measures, in Al-Madinah city, Saudi Arabia.